A Soldier’s Journey: Banyamulenge Narratives of Genocide - Davey, Christopher P. (Journal of interpersonal violence, 2021)
This article adds to debates in genocide studies on identity by analyzing Congolese Tutsi, or Banyamulenge, soldier narratives. It discusses this group’s identities and agency through the lens of the militarized generation of the 1990s. A conception of narrative identity is proposed that captures physical and relational networks as well as experiences of genocide. It examines fieldwork interviews conducted among former Banyamulenge soldiers and participants in the Alliance des Forces Démocratique pour la Libération du Congo-Zaïre (AFDL) and Rwandan Patriotic Army/Rwandan Patriotic Front (RPA/RPF). This narrative analysis uses open thematic coding to trace emplotment around three core themes: insecurity, marginalization, and destructive crises. In these narratives, genocide is conceptually utilized as a relational and discursive concept, and, therefore, permits an assessment of how participants understood and utilized the term. Doing so demonstrates the layering of victim and perpetrator identities, making a case for fluid identities in exposure to and with experiences of genocide. In the particular case of the Banyamulenge soldiers, they were active agents in the conflicts and events addressed in this article. Actors in genocide are agentic and engaged in the formation of fluid identity.